Burns results in profound muscle protein wasting in Sprague Dawley rats that is not resolved using the lipolysis inhibitor, acipimox. - Emre Vardarli; Nisha Bhattarai; Amina El Ayadi; Anesh Prasai; Victoria G Rontoyanni; Doaa Reda Abdelrahman; Andrew J Murton (PLoS ONE)
Introduction Major burns results in the rapid and profound accumulation of lipid in peripheral tissues, but its impact on muscle metabolic function is unclear. Given previous reports demonstrating that lipid oversupply compromises processes instrumental in the maintenance of muscle protein balance, we hypothesize that burn-induced lipid accumulation contributes to the loss of muscle mass with thermal injury. Methods To investigate this further, 48 male Sprague Dawley rats were randomized to undergo either a 60% total body surface area burn or sham procedure. To elucidate the impact of burn-induced lipid accumulation, animals were further subdivided to receive either acipimox (50 mg.kg-1 b.w.), a lipolysis inhibitor administered to deplete intramuscular lipids, or vehicle (PBS), daily for 7 days. Throughout, animals received deuterated water to permit the determination of muscle protein kinetics. Results Compared to sham animals, burn injury resulted in a 12% loss of gastrocnemius muscle mass (P < 0.001), paralleled by a 30 and 40 increase in the fractional synthetic and breakdown rates of gastrocnemius mixed proteins (P < 0.01), respectively, culminating in a 2-fold decline in net muscle protein (P < 0.01). Contrary to expectations, burns had no impact on muscle triglyceride content, while acipimox treatment failed to protect muscle mass, impact muscle triglyceride concentrations, or muscle protein kinetics. Conclusions In a rodent model of burns, the loss of muscle mass primarily occurs due to the acceleration of muscle proteolysis, independent of any change in muscle lipid content.